Numerical modeling of subcooled nucleate flow boiling in engine cooling systems - Öhrby, Fredrik (My University, 2014)
The demands for high power and low emissions put focus on energy efficiency when developing new engines. An important part is the engine cooling system, which cools the engine structure below damaging temperatures. For high temperatures in the cooling system there is a risk that boiling occurs and while the initial nucleate boiling enhances the cooling effect the subsequent film boiling decreases the heat transfer drastically. Volvo Cars therefore aims to develop a method that can predict the presence of boiling and estimate the heat transfer effects. As a first step, one-dimensional boiling models and correlations in combination with three-dimensional Computational Fluid Dynamics (CFD) analysis are investigated. A set of chosen models have been evaluated in Matlab and in the commercial CFD code Star-CCM+. An expression to predict the presence of boiling has successfully been implemented into the software and when applied to an engine cooling jacket, boiling is predicted to occur in those areas where it is expected. The heat transfer effects are estimated using the Chen correlation [1, 2] together with the Dry-spot model [3, 4, 5] with promising results but convergence issues appear for the Dry-spot model at high wall temperatures. A method has also been created to indicate the presence of critical film boiling and when applied to the engine cooling jacket, film boiling is indicated mainly in the cylinder head around the exhaust ports. Before including the developed methods in the standard analysis of the engine cooling jacket, further work is needed to improve and validate the estimations of the heat transfer and to solve the convergence issues.
Keywords: Hållbar utveckling; Grundläggande vetenskaper; Energi; Strömningsmekanik och akustik; Transport; Sustainable Development; Basic Sciences; Energy; Fluid Mechanics and Acoustics; Transport